Pengaruh Kepatuhan Pajak, Kewajiban Moral Sanksi Perpajakan, Kaulitas Pelayanan, Dan Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Jayapura) - Farid Trayayudha; Anthonius H. Citra Wijaya; Pascalina V. S Sesa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
Tax Compliance Costs, Moral Obligations, Tax Sanctions, Quality of Service and Application of E-Filing are among the factors affecting Taxpayer Compliance, so it needs to be improved. The purpose of this study is to determine the Effect of Tax Compliance Costs, Moral Obligations, Tax Sanctions, Quality of Service and Application of E-Filing to Taxpayer Compliance.The data collection technique used in this study was a questionnaire (Angket) with 100 WPOP respondents. The data analysis in this study was conducted quantitatively, using multiple linear regression statistical tools with the help of IBM SPSS 24 software. This is to find out the varaibel picture of Tax Compliance Costs, Moral Obligations, Tax Sanctions, Quality of Service and Application of E-Filing to Taxpayer Compliance.The results of this study prove that there is a significant influence between the variables of Moral Obligation and Quality of Service. Meanwhile, variable Tax Compliance Costs, Tax Sanctions, and E-Filing Implementation have no significant effect on Taxpayer Compliance.